VD_FINDINFO Décision / 2022 / 251 vom 25. Februar 2022 - VD Tribunal cantonal (2022)
ABUS D'AUTORITÉ, LÉSION CORPORELLE SIMPLE, DÉCISION D'IRRECEVABILITÉ | 123 CP, 126 CP, 14 CP, 312 CP, 310 CPP (CH), 24 LPol